Effect of phenolic compounds on the growth of selected probiotic and pathogenic bacteria - Pacheco Ordaz, R. (2018)
Fruit extracts from different tissues (pulp, seed and peel) have shown antimicrobial and prebiotic activities related to their phenolic profile, although structure-specific evaluations have not been reported yet. The effect of five phenolic compounds (catechin and gallic, vanillic, ferulic and protocatechuic acids) identified in different fruits, particularly in mango, was evaluated on the growth of two probiotic (Lactobacillus rhamnosusGG ATCC 53103 and Lactobacillus acidophilusNRRLB 4495) and two pathogenic (Escherichia coli 0157:H7 ATCC 43890 and Salmonella enterica serovar Typhimurium ATCC 14028) bacteria. The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) of phenolic acids ranged from 15–20 mmol l−1 and 20–30 mmol l−1 against E. coli and S. Typhimurium, respectively. For catechin, the MIC and MBC were 35 mmol l−1 and >35 mmol l−1 against E. coli and S. Typhimurium, respectively. The presence of catechin and gallic, protocatechuic and vanillic acids in MRS broth without dextrose allowed the growth of lactobacilli. Catechin combined with protocatechuic or vanillic acid mildly allowed the growth of both probiotics. In conclusion, phenolic compounds can selectively inhibit the growth of pathogenic bacteria without affecting the viability of probiotics. Significance and Impact of the Study: This study provides relevant information about the effects of phenolic compounds commonly present in fruit and vegetables on the growth of probiotic and pathogenic bacteria. The compounds selectively allowed the growth of probiotic lactobacilli (Lactobacillus rhamnosus GG and Lactobacillus acidophilus) and inhibited pathogenic bacteria (Escherichia coli and Salmonella Typhimurium) at the same concentration (20 mmol l−1). These findings can contribute to the formulation of nutraceutical products, such as synbiotics, that can restore or maintain an optimal composition of human microbiota, potentially improving the overall health of the consumer.